Clinical efficacy of hydrochloric acid and phosphoric acid in microabrasion technique for the treatment of different severities of dental fluorosis: An in vivo comparison - Dipanshu Kumar; Aparna Singh; Chitrita Gupta Mukherjee; Asib Ahmed; Arpanna Singh; Mukesh Kumar Hasija; Siddharth Anand (Wolters Kluwer Medknow Publications, 2019)
Aim: The aim of this study was to evaluate and to compare the clinical efficacy of two compounds (hydrochloric acid and phosphoric acid) in microabrasion in terms of degree of stain removal (DSR) and improvement of appearance for the different severities of dental fluorosis. The mean time and number of applications required by the two experimental compounds were also compared. Methodology: Children between the age group of 9-14 years with dental fluorosis to two or more fluorozed anterior permanent teeth were included in the study. The Dean's Fluorosis Index was used to classify each tooth, and they were randomly selected into mild (Group I), moderate (Group II), and severe (Group III) groups of fluorosis. Ten teeth from each of these groups were randomly allotted for undergoing microabrasion using 18% HCl with pumice and other 10 teeth using 37% phosphoric acid with pumice. Colored preoperative and postoperative photographs were taken for each patient and analyzed for improvement in appearance and DSR. Time and number of applications and parent-patient response with both the compounds were also recorded. The results were tabulated and statistically analyzed. Results: The results of the present study showed that a nonsignificant difference existed in DSR and improvement in appearance between the two compounds of microabrasion for all the three degrees of dental fluorosis. Significantly lesser time was taken by HCl in mild and moderate fluorosis. Significantly lesser number of applications was required with HCl for moderate fluorosis. Nonsignificant difference existed for parent-patient response with both the compounds for all the severities of dental fluorosis. Conclusion: 18% HCl with pumice and 37% phosphoric acid with pumice both can be used for microabrasion for all the severities of dental fluorosis. The time and number of applications using HCl were lesser; therefore, it should be preferred over H3PO4 for all the severities of fluorosis.